1979
DOI: 10.1159/000128067
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Vagotomy on Bile Kinetics in the Rhesus Monkey

Abstract: An increased incidence of gallstones has been reported following truncal vagotomy and gastric drainage but never conclusively proven. In the Rhesus monkey, bile composition and flow is similar to man. A model of biliary drainage was established which permits continuous monitoring of bile kinetics. Following truncal vagotomy and pyloroplasty, a significant fall in bile acid concentration was observed, accompanied by a rise in cholesterol concentration. This resulted in an overall rise in cholesterol saturation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…bladder bile composition after gastrectomy and vagotomy have reported the increased cholesterol lithogenicity of gallbladder bile [8,9], whereas other have failed to prove this [10][11][12], We have shown that the type of gall bladder stones was brown pigment in 36%, black pigment in 32%, and cholesterol in 32% of 44 patients who had previously un dergone gastrectomy [13]. Nevertheless, most studies on gallbladder bile lithogenicity after gastrectomy and vagotomy have focused on the risk factors for cholesterol gallstone for mation.…”
Section: Introductionmentioning
confidence: 99%
“…bladder bile composition after gastrectomy and vagotomy have reported the increased cholesterol lithogenicity of gallbladder bile [8,9], whereas other have failed to prove this [10][11][12], We have shown that the type of gall bladder stones was brown pigment in 36%, black pigment in 32%, and cholesterol in 32% of 44 patients who had previously un dergone gastrectomy [13]. Nevertheless, most studies on gallbladder bile lithogenicity after gastrectomy and vagotomy have focused on the risk factors for cholesterol gallstone for mation.…”
Section: Introductionmentioning
confidence: 99%